The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7883/yoken.jjid.2020.181
|View full text |Cite
|
Sign up to set email alerts
|

The First Pediatric Patients with Coronavirus Disease 2019 (COVID-19) in Japan: Risk of Co-Infection with Other Respiratory Viruses

Abstract: The first pediatric patients with coronavirus disease 2019 (COVID-19) in Japan;The risk of co-infection with other respiratory viruses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Cough: Initial symptoms were fever and cough; even among neonates 30 . Cough was experienced by the majority of patients, 10‐12,14,15,19,21‐93 it was mainly dry, but was sometimes followed by productive cough in moderately severe cases 19 . There may be upper airway symptoms, such as nasal congestion, rhinitis, and sore throat 19 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cough: Initial symptoms were fever and cough; even among neonates 30 . Cough was experienced by the majority of patients, 10‐12,14,15,19,21‐93 it was mainly dry, but was sometimes followed by productive cough in moderately severe cases 19 . There may be upper airway symptoms, such as nasal congestion, rhinitis, and sore throat 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Fever: One of the commonest early symptoms is fever, 11,14,15,19‐22,25‐36,38‐58,61‐65,67,68,70‐106 occasionally low grade. In Zhejiang province, fever clinics that exclusively accept for admission patients suspected of being positive for SARS‐CoV‐2 were set up 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of COVID-19, a small series of patients also found coinfections among children. 192 In contrast, however, studies from Norway and Kenya found an equal number of coronavirus identifications among both symptomatic and asymptomatic controls. 140,141 When some of these populations were also analyzed for episodes of coronavirus coinfections with other viruses, both groups had an approximately 68% frequency out of the total coronavirus infections.…”
Section: Studies Of High Putative Cofactor Incidencesmentioning
confidence: 93%
“…During the beginning of the COVID-19 spread in Japan, influenza and human metapneumovirus were prevalent among children (the study was performed in the Furano region). Three children were diagnosed with COVID-19, two of whom were co-infected with influenza and human metapneumovirus [59].…”
Section: Co-infection Of Sars-cov-2 With Influenza-like Virusesmentioning
confidence: 99%